Strategic Management of Reverse Logistics in Sustainable Electronics Supply Chains - Aktar, Suborna (My University, 2025)
The global expansion of electronic production and consumption has intensified the challenge of managing end-of-life electrical and electronic equipment. Reverse logistics has therefore become central to achieving sustainability and regulatory compliance. This thesis explores how governance design, firm capabilities, and digital analytics interact to influence operational performance in electronics reverse logistics. It specifically investigates how governance decisions are translated into measurable outcomes, what capability bundles and network architectures enhance performance, and how digital and sustainability analytics improve environmental predictability. A systematic synthesis of peer-reviewed research, official program portals, and archival audits of Extended Producer Responsibility (EPR) and Producer Responsibility Organization (PRO) systems from 2015 to 2025 reveals a fragmented but evolving governance landscape. National and regional schemes vary in their auditability, target alignment, accessibility to producers, and the quality of reporting. The literature emphasizes the significance of auditable data trails, preparation-for-reuse recognition, and rural-access provisions in stabilizing collection networks. Firm-level evidence also highlights that strategic capability development—such as digital traceability, capacity planning, and third-party reverse logistics (3PRL)—improves cost control and responsiveness under uncertain return flows. Empirical evaluation, guided by PRISMA methodology, integrates findings across two levels: the system level and the firm level. Results indicate that transparent governance frameworks and adaptive firm capabilities collectively enhance throughput efficiency, reduce greenhouse gas emissions, and enable traceable recovery of critical raw materials. Preparation-for-reuse and certified remanufacturing outperform direct recycling in both speed and environmental benefit. The findings support the hypothesis that well-structured governance and capability-driven management translate into tangible operational, environmental, and financial advantages, offering practical insights for policymakers and industry managers.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management